2019
DOI: 10.21873/invivo.11477
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Pro-inflammatory Properties of Aliphatic Alpha, Beta-unsaturated Acid and Ester Monomers in RAW264.7 Cells and Their Chemical Reactivity

Abstract: Background/Aim: α,β-Unsaturated ester monomers such as methyl methacrylates (MMA), 2-hydroxyethyl methacrylates (2-HEMA), ethyleneglycol dimethacrylate (EGDMA) and triethyleneglycol dimetacrylate (TEGDMA) have been widely used in dentistry as dental materials. The present study was designed to clarify the proinflammatory activity of monomers. Materials and Methods: The cytotoxicity of the monomers and their effects on the expression of cyclooxygenase-2 (Cox2), nitric oxide synthase 2 (Nos2) and heme oxygenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, excess ROS production can cause peripheral tissue and cellular damage, DNA damage, lipid peroxidation, and pro-inflammatory response [ 14 , 15 , 16 ]. Recent several studies have shown that cytotoxicity was induced by TEGDMA in RAW264.7 macrophages via their large interaction potency and impregnation into lipid bilayers [ 17 ]. The incubation of macrophages with TEGDMA leads to various proinflammatory responses, such as the upregulation of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excess ROS production can cause peripheral tissue and cellular damage, DNA damage, lipid peroxidation, and pro-inflammatory response [ 14 , 15 , 16 ]. Recent several studies have shown that cytotoxicity was induced by TEGDMA in RAW264.7 macrophages via their large interaction potency and impregnation into lipid bilayers [ 17 ]. The incubation of macrophages with TEGDMA leads to various proinflammatory responses, such as the upregulation of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…41 For monomer HEMA and crosslinker EGDMA, although they are widely used in biomedical areas it was reported that HEMA could induce apoptosis and cell-cycle delay 38,39 and EGDMA could exert proinflammatory activities. 40 To remove these compounds, the UV-cured PHEMA films were washed rigorously with PBS. As shown in Figure 10, the cells seeded on the washed films presented high viability, suggesting significantly improved biocompatibility of the films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The biocompatibility and cytotoxicity of photoinitiators are always a big concern for their biomedical applications . For monomer HEMA and cross-linker EGDMA, although they are widely used in biomedical areas it was reported that HEMA could induce apoptosis and cell-cycle delay , and EGDMA could exert proinflammatory activities . To remove these compounds, the UV-cured PHEMA films were washed rigorously with PBS.…”
Section: Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanisms identified were the radical reactivity of MA and derivatives with cellular nucleophiles such as glutathione. MA has also been shown to directly induce DNA damage and inhibit key metabolic enzymes (Plaga et al, 2000;Ansteinsson et al, 2013;Arya et al, 2013;Curson et al, 2014;Murakami et al, 2019). This toxicity makes its direct biological production highly limited in any of the potential microbial hosts considered.…”
Section: Direct Production Of Methacrylic Acidmentioning
confidence: 99%